The Effect of Intravenous Dexmedetomidine on Postoperative Pain Intensity in Patients undergoing Abdominal Hysterectomy - Nesioonpour, Sholeh; Behaeen, Kaveh; Mohtadi, Ahmad Reza; Ghomeishi, Ali; Babadi, Negin (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The control of perioperative pain and its practice can play an important role in short and long term postoperative convalescence. The aim of this study was to evaluate the effect of dexmedetomidine on postoperative pain in patients undergoing abdominal hysterectomy (TAH). Methods: This double-blind, randomized controlled clinical trial study was conducted on 70 women aged 35-65 years undergoing general anaesthesia for TAH. In dexmedetomidine group, immediately after induction, a bolus dose of dexmedetomidine 1 μg/kg was injected for 15 minutes and then a dose of infusion 0.5 μg/kg until the end of surgery. In the control group, normal saline was injected. Patients were evaluated for pain intensity according to the visual analogue scale (VAS), the amount of analgesic use during 24 hours after surgery and time of administration of the first dose of pethidine. Results: Although the mean pain intensity at all times in dexmedetomidine group was lower than the control group, there was a significant difference at 4, 8, 16, and 24 hours after surgery (P <0.05). The time of the first request for administration of the first dose of pethidine was greater than the control group, but there was no significant difference in first-time administration of opioid in the two groups (P >0.05). Although the mean dose of pethidine was lower in the dexmedetomidine group, there was no statistically significant difference between the mean values in the two groups (P >0.05). Conclusion: This study showed the efficacy of dexmedetomidine in reducing post-operative pain and receiving pethidine after surgery.